2018
DOI: 10.1590/0100-6991e-20181756
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nicotine patch in pain control of patients undergoing laparoscopic cholecystectomy

Abstract: although pain levels were lower for nicotine within 24 hours, the action of nicotine and the need for rescue opioids in pain control were not statistically significant between the groups and at the time intervals studied. There was no clinical repercussion in the hemodynamic parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Moreover, in the study by Turan et al, intraoperative use of nicotine patch and opioids did not reduce the amount of postoperative pain after gynecological surgery. 32 Nevertheless, Martins et al 33 analyzed 17 patients under laparoscopic cholecystectomy and observed that despite the low pain score for the nicotine group at 24 hours, nicotine was not effective in controlling pain at the time intervals of the study. In addition, it has been shown in various studies that nicotine can cause hypoxia in tissues as a vasoconstrictor and also by increasing the concentration of calcium ions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the study by Turan et al, intraoperative use of nicotine patch and opioids did not reduce the amount of postoperative pain after gynecological surgery. 32 Nevertheless, Martins et al 33 analyzed 17 patients under laparoscopic cholecystectomy and observed that despite the low pain score for the nicotine group at 24 hours, nicotine was not effective in controlling pain at the time intervals of the study. In addition, it has been shown in various studies that nicotine can cause hypoxia in tissues as a vasoconstrictor and also by increasing the concentration of calcium ions.…”
Section: Discussionmentioning
confidence: 99%